(untitled) (CAHIERS MAGELLANES-NS, 2024)
The aim of a gamified recruiter app is to provide a fun and interactive way for recruiters to manage their job postings, applicants, and other data, and make data-driven decisions to improve their job search and retention. The objective of the app is to help recruiters increase the efficiency and effectiveness of their job search process, and to provide them with valuable insights into their applicant pool. A gamified recruiter app can be a fun and interactive way for recruiters to manage their job postings, applicants, and other data. Gamifying the job search process can have a range of benefits for recruiters and job seekers. [1] For recruiters, gamifying the process can increase engagement and motivation among their job seekers, which can lead to increased job offers and better hires. [2] For job seekers, gamifying the process can help them stay motivated and engaged in the job search process, which can lead to better job prospects and increased job satisfaction. A gamified recruiter app can have a significant impact on academic performance by increasing engagement and motivation among students. Overall, a gamified recruiter app can have a significant impact on academic performance by increasing motivation, retention of information, engagement, problem-solving skills, and critical thinking skills.